К вопросу о создании коммерческого варианта боеприпаса с применением N&L-технологии - Нелаев, В. П.; Акуленко, В. Л.; Пепеляев, И. А. (НТУ "ХПИ", 2010)
For creation of practical pre-conditions for modernization and test of new native ammunition on modern methodological basis that does not have analogues, structure of experimental scientific laboratory is offered, and estimate information about necessary personnel, material and financial resources, plan-graph of conducting of experimentally-searching works for creation of propellant charges of new qualities is presented. In obedience to the resulted estimations, for creation of commercial variant ammunition example of caliber less than 30-мм with elements N&L-technology on the chart of temporal N&L-laboratory it will be needed approximately 80 thousands USD, 26 weeks (6 months) time, command of specialists on 7 persons, reliable agreement relations with the specialized enterprises.
Keywords: артиллерийский выстрел; снаряд; огневые испытания; заряд; пробные образцы